Aerobic Oxidative Intramolecular Aromatic Coupling via Heterogeneous Metal Catalysts. Issue 19 (12th September 2016) - Fujimoto, Shigenobu; Matsumoto, Kenji; Shindo, Mitsuru
Abstract: An aerobic, heterogeneously catalyzed oxidative intramolecular coupling reaction of aromatic compounds is reported here. Using commercially available, recyclable heterogeneous metal catalysts, the coupling reactions of o ‐terphenyls and 1, ω‐biarylalkanes proceeded quickly under mild conditions, i.e., at room temperature under oxygen as a co‐oxidant almost all within 1 h, to provide the corresponding coupled products like triphenylenes and phenanthrenes in good to excellent yields. This reaction is an easily handled, practical, and atom‐economical coupling method, which is of great importance in modern organic syntheses. Abstract :